THE IMPOSITION OF LAND AND BUILDING FORESTRY TAX BASED ON GOVERMENT REGULATION NUMBER 25 OF 2002 (Study In Association of Indonesian Forest Concessionaires Holders Office) - Megista Novinagari (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
In writing a thesis the researcher discusses about The Imposition Of Land And Building Forestry Tax Based On Goverment Regulation Number 25 Of 2002. The imposition PBB of forestry will be a excess or deficiency.Tax payment must be paid by forest concessionaires holder. Besides that the imposition PBB forestry has heavy was not efficient, the researcher will analize the implementation in the field. The approach method used in this thesis is Juridical-Empirical, discusses and analize the legal issues which is set by juridical with towards fact empirical in the field. Data analysis technique used is descriptive qualitative.Based on the research writer have outcomes, that implementation is still held by businessmen forest, with the process of payments are not complicate entrepreneurs the forest as taxpayer.But no, with total NJKP according to government regulation no 25 2002.Njkp to 40 % ineffective when worn on land forest.See facts in the field we need to hope the government do the review against imposition pbb in the forest.Keyword: Land and Bulilding tax, foresty tax, forest concessionaires holder